War on Drugs: The Church’s Resilient Mission of Resistance - Fung, Jojo M., SJ (Archīum Ateneo, 2018)
The war on drugs has become contentious in the public and private spaces in this nation. What is contested is the defensibility of an immoral means that legitimizes killing and collateral damage in the guise of upholding the public safety at the expense of the human security of the poor and the dispensable drug-pushers and addicts from the poorer neighborhoods. In light of the teachings of the Catholic Bishops’ Conference of the Philippines (CBCP), Association of Major Religious Superiors of the Philippines (AMRSP), the Manila Episcopal Area of the United Methodist Church and the evaluative framework of the just war theory, the use of EJK as a legitimate means and use of the term ‘war’ are debunked as indefensible. The truth-telling of two former death squad members is a strong indictment of EJK and the militaristic connotation of the term ‘war on drugs’ with the subsequent violation of the dignity and security of the weak. The more sustainable means of safeguarding the public safety of the weak in particular is the recourse to viable strategies related to the Drug Education & Harm Reduction Policies and Programs implemented by the Church and civil society in response to their official pronouncements.